An Overview of Appetite-Regulatory Peptides in Addiction Processes; From Bench to Bed Side - Shevchouk, Olesya T.; Tufvesson-Alm, Maximilian; Jerlhag, Elisabet (Frontiers in Neuroscience, 2021)
There is a substantial need for new pharmacological treatments of addiction, and appetite-regulatory peptides are implied as possible candidates. Appetite regulation is complex and involves anorexigenic hormones such as glucagon-like peptide-1 (GLP-1) and amylin, and orexigenic peptides like ghrelin and all are well-known for their effects on feeding behaviors. This overview will summarize more recent physiological aspects of these peptides, demonstrating that they modulate various aspects of addiction processes. Findings from preclinical, genetic and experimental clinical studies exploring the association between appetite-regulatory peptides and the acute or chronic effects of addictive drugs will be introduced. Short or long-acting GLP-1 receptor agonists independently attenuate the acute rewarding properties of addictive drugs or reduce the chronic aspects of drugs. Genetic variation of the GLP-1 system is associated with alcohol use disorder. Also, the amylin pathway modulates the acute and chronic behavioral responses to addictive drugs. Ghrelin has been shown to activate reward-related behaviors. Moreover, ghrelin enhances, whereas pharmacological or genetic suppression of the ghrelin receptor attenuates the responses to various addictive drugs. Genetic studies and experimental clinical studies further support the associations between ghrelin and addiction processes. Further studies should explore the mechanisms modulating the ability of appetite-regulatory peptides to reduce addiction, and the effects of combination therapies or different diets on substance use are warranted. In summary, these studies provide evidence that appetite-regulatory peptides modulate reward and addiction processes, and deserve to be investigated as potential treatment target for addiction.